A comparative analysis among some specialized publications on education in Latin America - Botero Lozano, Sofía; Chaves Castillo, Nicolás; Contreras López, Lina; Rojas Calderón, Felipe; Rubiano Sanabria, Juan; Salas Gómez, Sergio; Sánchez Parra, Diego (Universidad Antonio Nariño, 2021)
Education is fundamental for the construction of each individual part of a society in every country. The development of a country is evaluated based on its level of education, even if it is not a conscious act. This paper is an exploratory study where the topics of Colombian investigative ublications are compared to those of other Latin American journals in order to judge what kind of impact they have on existing social issues in each country.